Conformal invariants : topics in geometric function theory - Ahlfors, Lars Valerian (New York : McGraw Hill Education, 1973)
This is a textbook primarily intended for students with approximately a year's background in complex variable theory.
1. Applications of Schwarz's lemma -- 2. Capacity -- 3. Harmonic measure -- 4. External length -- 5. Elementary theory of univalent functions -- 6. Loewner's method -- 7. The schiffer variation -- 8. Properties of the external functions -- 9. Riemann surfaces -- 10. The uniformization theorem.
Includes bibliographical references and index.
Keywords: DIFFERENTIAL EQUATIONS